116 Paraneoplastic progressive-supranuclear palsy like brainstem syndrome associated with lung adenocarcinoma. (23rd August 2021) - Gerbis, Natasha; Fontes-Villalba, Ariadna; Aouad, Patrick; Fernando, Suran; Parratt, John DE
Abstract : Objectives: Progressive supranuclear palsy (PSP) is a neurodegenerative condition characterised by Parkinsonian features, cervical dystonia and ophthalmoparesis. Paraneoplastic PSP has previously been reported in the literature in association with several different cancer types but is very rare. 1–3 Methods: Case review. Results: A 74 year old Chinese man was diagnosed with Stage 1b EGFR positive lung adenocarcinoma and underwent a left upper lobectomy. Twelve months later he presented with rapidly progressive neck stiffness, reduction in motor function and gait (over 8 weeks) and recalcitrant disequilibrium. He had hypomimia, frontalis over-activation, blepharospasm, blepharotremor and a supranuclear gaze palsy. There was marked axial rigidity, bradykinesia and cervical dystonia. An MRI brain and spine were unremarkable. Vestibular function tests were normal. Serum antineuronal antibodies were negative. The CSF analysis was unremarkable. The patient responded to plasma exchange on a two to three-weekly basis with significant improvement in saccadic eye movements and Parkinsonism. However, disequilibrium remained a persistent problem despite the discovery and excision of a second EGFR wild type non-small cell lung cancer, and Rituximab was recently started. Cervical dystonia was treated partially with Botulinum toxin injections, but the patient responded poorly to L-dopa. Conclusions: This suspected paraneoplastic disease exhibits several features of PSP. In particular, the supranuclear palsy, Parkinsonism and dystonia are similar to the typical syndrome. However, the rapidly progressive presentation and disequilibrium are unusual and a response to plasma exchange, suggests humorally mediated neuronal pathology. In rapidly evolving PSP-like cases with cancer, investigation for immunopathology is warranted. References: Dash D, Choudhary R, Ramanujam B, Vasantha PM, Tripathi M. Paraneoplastic syndrome mimicking progressive supranuclear palsy. J Clin Neurosci 2016 Oct;32 :162–3. doi:10.1016/j.jocn.2016.02.032. Epub 2016 Jun 16. PMID: 27318371. Takkar A, Mehta S, Gupta N, Bansal S, Lal V. Anti- RI antibody associated progressive supranuclear palsy like presentation in a patient with breast carcinoma. J Neuroimmunol 2020 Oct 15;347 :577345. doi:10.1016/j.jneuroim.2020.577345. Epub 2020 Jul 26. PMID: 32763584. Tan JH, Goh BC, Tambyah PA, Wilder-Smith E. Paraneoplastic progressive supranuclear palsy syndrome in a patient with B-cell lymphoma. Parkinsonism Relat Disord 2005 May;11(3):187–91. doi:10.1016/j.parkreldis.2004.09.003. PMID: 15823484.